漢詩 書畫典故 翻譯의 오류 및 대안에 관한 일고 - 왕아남 (동양한문학연구, 67(0), 2024)
論書詩·題畫詩를 비롯한 書畫詩에 書畫典故이(가) 대량으로 사용되고, 일부 書畫典故를 이해하는 데 전문적인 서화 지식이 필요하기 때문에 書畫典故의 번역 작업이상당히 어려운 작업이라고 할 수 있다. 이에 따라 번역 과정에 書畫典故의 누락 및 오역이 생길 수밖에 없다. 한국고전종합DB에 수록한 한시 번역문을 살펴보면 현재의 書畫典故의 翻譯에는 書畫對語의 모호화, 書畫典故의 누락, 書畫典故의 오역이라는 세 가지 주요 문제가 있음이 분명하다. 우선, 書畫對語의 모호화란 주어의 모호화를 말한다. 書畫對語는 동물이나 경물을 담긴 네 글자로 그림 혹은 글씨를 묘사하는 용어이다. 즉 比擬의 수법으로 작품의 미학적 특징을 드러내는 것이다. 따라서 번역할 때 문장의 주어가 동물이나 경물이 아닌 글씨(그림)라는 사실을 반드시 밝혀야 한다. 鳳翥龍蟠·虎臥龍跳 등 動態 對語는 ‘V + 은/는 듯’이라는 도식에 따라 번역할 수 있고, 春蚓秋蛇·家雞野鶩 등 靜態 對語는 ‘N +처럼’이라는 도식에 따라 번역할 수 있다. 다음에 書畫典故의 누락은 또한 흔히 보이는 번역 오류 중의 하나다. 마지막으로 전문적 서화 지식이 결핍으로 書畫家의 이름·작품명을 일반 詩語로 착각하여 書畫家의 字號·작품명 등을 잘못 번역할 수도 있다. 이런 문제점을 해결하기 위해 다음과 같은 대안을 마련해봤다. 첫 번째, 書畫典故의 근원을 찾는다. 해동 한시와 중국 한시 간의 傳承 關係를 가지고 있기 어느 정도 그 근원을 확인할 수 있다. 해동 문인은 李白·杜甫·韓愈·蘇軾等 시인의 10여 수 한시에 담긴 82개 書畫典故를 적극적으로 수용해 왔다. 10여 수 한시에 담긴 82개 書畫典故를 익히면 海東漢詩에 인용된 書畫典故를 전체적으로 파악할 수 있을 뿐만 아니라 書畫典故의 번역에도 도움이 될 수 있다. 두 번째, 書畫典故 platform을 구축한다. 한국고전종합DB에 수록된 漢詩 database를 바탕으로 하여 하위 database인 書畫典故 platform을 구축한다. 누구나 이 platform에 漢詩 書畫典故의 출전·뜻풀이·용례에 관한 정보를 편집할 수 있고, 편집된 정보는 전문가·역자의 검수를 거쳐 공식적으로 공개할 수 있다. 세 번째, multimedia를 활용한다. 전통적인 텍스트 외에도 그림·영상 등 multimedia를 활용함으로써 書畫典故를 더 직관적으로 이해할 수 있다. Chinese poetry, particularly in the realm of calligraphy and painting, often employs a multitude of allusions, posing challenges for translators due to the complexity and diverse sources of these allusions. This paper explores the common errors encountered in translating these allusions, focusing on the areas of subject confusion, omissions, and semantic inaccuracies. The analysis is based on the examination of Korean translations of Chinese poetry found in the Comprehensive Korean Classics Database. Firstly, subject confusion errors are prevalent in translating calligraphy and painting allusions, especially in dynamic expressions. It is crucial to explicitly convey the use of simile in the translated text, such as employing the form ‘V + 은/는 듯’ for dynamic expressions like ‘鳳翥龍蟠’. For static expressions like ‘春蚓秋蛇’ , the translation can adopt the form ‘N +처럼’. Secondly, omission errors are common in the translation of calligraphy and painting allusions. These omissions can lead to a loss of meaning and should be addressed through careful examination of the original text. Lastly, the lack of specialized knowledge in calligraphy and painting may result in the confusion of artists' names or artwork titles with general poetic language, leading to translation errors in terms of artist names, work titles, and related allusions. Given the frequent occurrence and complexity of calligraphy and painting allusions in Chinese poetry, achieving flawless translations is challenging. However, demanding translators to possess an extensive knowledge of calligraphy and painting may be impractical. This paper proposes three strategies to strike a balance between accuracy and accessibility: Tracing the Origin of Calligraphy and Painting Allusions: By recognizing the influence and transmission of Chinese poetry, particularly the impact of poets like Li Bai, Du Fu, Han Yu, and Su Shi, translators can focus on key works that embody calligraphy and painting allusions. This foundational understanding forms the basis for higher-quality translations. Building a Database for Calligraphy and Painting Allusion Data: Utilizing the Korean Comprehensive Classics Database, a platform can be constructed to compile data on calligraphy and painting allusions, their origins, interpretations, and usage examples. This platform allows collaborative editing, with domain experts and scholars ensuring accuracy and completeness. Utilizing Multimedia for Enhanced Learning: Employing interactive learning through the data platform and utilizing multimedia resources can provide an intuitive and visual understanding of calligraphy and painting allusions, including their meanings and usage examples. KCI Citation Count: 0